The Moxibustion-Induced Thermal Transport Effect Between the Heart and Lung Meridians With Infrared Thermography - Li, Xiaoyu; Jiang, Yongliang; Hu, Hantong; Lou, Jiali; Zhang, Yajun; He, Xiaofen; Wu, Yuanyuan; Fang, Junfan; Shao, Xiaomei; Fang, Jianqiao (Frontiers in Cardiovascular Medicine, 2022)
Objectives: By comparing the differences in the thermal transport effect between the heart and lung meridians induced by moxibustion, this study aimed to investigate the specificity of site-to-site associations on the body surface between different meridians. Methods: Eighty healthy participants were divided into the heart meridian intervention group and the lung meridian intervention group; moxibustion was performed at these two meridians, respectively. Baseline temperature and its change magnitude from baseline induced by moxibustion in 6 measuring sites of the heart and lung meridians were assessed by infrared thermography (IRT). Results: In the lung meridian intervention group (moxibustion over LU5), the temperature of the distal sites in the lung meridian increased significantly at 5, 10 and 15 min compared with pre-moxibustion (P < 0.001). The temperature of site 4 in the heart meridian, which was nearest to the moxibustion site, increased significantly compared with pre-moxibustion (P < 0.05), while the temperature in the distal sites of the heart meridian did not differ significantly during moxibustion. Regarding the comparison of temperature change magnitude from baseline (△T) between the two meridians, the △T of site 2 in the lung meridian was significantly higher than site 4 in the heart meridian at 5 and 10 min after moxibustion (P < 0.05), despite that site 2 was more distal from the moxibustion site than site 4. Similarly, the △T of site 3 in the lung meridian was significantly higher than site 5 and site 6 in the heart meridian at 5, 10 and 15 min after moxibustion (P < 0.05). In the heart meridian invervention group, similar thermal transport effect between the two meridians was observed. The thermal transport effect of the distal sites along the heart meridian was more significant than that of the site closer to the moxibustion site but located in the lung meridian. Conclusions: In the heart and lung meridians, the moxibustion-induced thermal transport effect is closely related to meridian routes, not just related to the absolute distance from the moxibustion site, thereby confirming the relative specificity of "site-to-site" associations on the body surface in these two meridians.